Child and Family Team Meeting Characteristics and Outcomes in a Statewide System of Care. Issue 3 (8th March 2019) - Schreier, Alayna; Horwitz, Mark; Marshall, Tim; Bracey, Jeana; Cummins, Mary; Kaufman, Joy S.
Abstract: Systems of care (SOC) have relied on the wraparound care process to individualize community‐based services for children and youth with serious emotional and behavioral difficulties. A core element of wraparound care is Child and Family Team meetings (CFTs), which are designed to give youth and families a leadership role in developing and guiding their plan of care. The National Wraparound Initiative (NWI) has identified Practice Standards regarding CFT implementation. This study examined CFT characteristics and the association between those characteristics and youth and family outcomes in a statewide SOC. Participants were 363 youth ( M age   = 10.89, SD  =   3.72) and their caregivers. Families completed measures of youth and caregiver functioning and symptoms at enrollment and 6‐month follow‐up. Care coordinators completed a survey assessing CFT implementation and characteristics following each meeting. Multiple regression analyses were used to examine the relationship between CFT characteristics and youth and caregiver outcomes. Results indicated that a higher number of CFTs was associated with poorer outcomes, while a higher percentage of natural supports at meetings was associated with better youth outcomes. Number of days to the first CFT was associated with greater caregiver strain. Implications for CFT implementation within wraparound are discussed. Highlights: Significant relationships were observed between CFT characteristics and youth and family outcomes. A higher number of CFTs was associated with poorer youth and family outcomes. A higher percentage of natural supports was associated with better youth outcomes. SOCs may have difficulty in fully implementing CFTs consistently with NWI Practice Standards.